2004
DOI: 10.1073/pnas.0403486101
|View full text |Cite
|
Sign up to set email alerts
|

Three-body interactions improve the prediction of rate and mechanism in protein folding models

Abstract: Here we study the effects of many-body interactions on rate and mechanism in protein folding by using the results of molecular dynamics simulations on numerous coarse-grained C ␣ -model single-domain proteins. After adding three-body interactions explicitly as a perturbation to a Go -like Hamiltonian with native pairwise interactions only, we have found (i) a significantly increased correlation with experimental values and folding rates, (ii) a stronger correlation of folding rate with contact order, matching … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
113
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(124 citation statements)
references
References 63 publications
7
113
1
Order By: Relevance
“…These polarization effects likely induce a many-body cooperative component to the stacking interaction for coarse-grained bases, resulting in a much stiffer potential surface for local fluctuations around the native structure. Similarly, many-body interactions between coarse-grained residues in proteins were necessary to effectively capture protein folding rates and mechanisms 53 .…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…These polarization effects likely induce a many-body cooperative component to the stacking interaction for coarse-grained bases, resulting in a much stiffer potential surface for local fluctuations around the native structure. Similarly, many-body interactions between coarse-grained residues in proteins were necessary to effectively capture protein folding rates and mechanisms 53 .…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Analytical theory (24) and simulation studies, both on-and off-lattice (25)(26)(27), show that nonadditivity increases the magnitude of folding free-energy barriers. The larger cooperative effects of a nonadditive solvent averaged potential improves the accuracy of predicted protein folding rates and mechanisms, as clearly pointed out by Plotkin and coworkers (28). The goal of this study is to add the structural details of the heme cofactor to these simple protein topology-based models, which usually omit cofactors.…”
mentioning
confidence: 99%
“…The nonadditivity corrections to the barrier heights for folding to the two structures were calculated by introducing such nonadditivity as a perturbation to the pairwise additive Go model. Plotkin and coworkers (26) showed that these perturbations yield higher barriers that more closely fit experiment. The Rop dimer corrections not only change the absolute barrier heights but also increase the relative rate differences.…”
mentioning
confidence: 99%